Evaluasi Usability SIAM Universitas Mulia dengan Metode SUS - Frisca Bernadeta Caroline; Aisyah Nur Nailah Atikah; Yustian Servanda; Rizky Gandarrityaz (Nolsatu Publisher, 2026)
The Student Academic Information System (SIAM) is an information system for managing academic data at Mulia University Balikpapan (UM). Although this system has helped students access academic services, there are still issues related to ease of use between systems. Therefore, this study was conducted to assess the usability level of the SIAM interface using the System Usability Scale (SUS) method. This study used a quantitative approach with a SUS questionnaire distributed to active students of Mulia Balikpapan University who had experience using SIAM. The data obtained was analyzed to determine the usability category of the system and identify the obstacles perceived by users. Based on data calculations, an average score of 60.69 was obtained, reflecting the system's position in the Marginal High category. Technically, this score refers to a D grade scale with an OK adjective rating. Although the system is functionally capable of accommodating user needs, the data indicates that optimization of design elements is still necessary. These findings confirm that SIAM Universitas Mulia has reached a threshold of acceptable acceptance, but still requires some adjustments to achieve optimal usability performance. The results of this study are expected to provide useful input for the development and refinement of the SIAM interface so that it can improve user comfort, efficiency, and satisfaction in supporting academic activities.